2019
DOI: 10.1111/jopy.12449
|View full text |Cite
|
Sign up to set email alerts
|

Writing about life story chapters increases self‐esteem: Three experimental studies

Abstract: Objective: The purpose of the present three studies was to examine experimentally whether writing about life story chapters would increase self-esteem, self-concept clarity, and meaning.Method: In study 1, 179 participants rated state self-esteem and self-concept clarity before and after they described either four important life story chapters or four famous Americans. In study 2, 141 new participants completed a similar procedure to study 1 and then returned two days later to complete the procedure a second t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 57 publications
4
18
0
Order By: Relevance
“…Thus, chapters may be more salient to narrative identity than specific memories. Indeed, studies have shown that chapters are rated as more important to identity than specific memories (Steiner et al, 2018;.…”
Section: 1narrative Identity: Past and Future Life Story Chaptersmentioning
confidence: 99%
“…Thus, chapters may be more salient to narrative identity than specific memories. Indeed, studies have shown that chapters are rated as more important to identity than specific memories (Steiner et al, 2018;.…”
Section: 1narrative Identity: Past and Future Life Story Chaptersmentioning
confidence: 99%
“…Expressive writing therapy with the theme of the client's life story experience has a positive impact on the client's ability to assess herself that she can survive until the present time, despite unpleasant events that happened in her life. Research shows that writing about life stories can increase selfesteem and suggests that building positive self-esteem may be an important function of life stories (Steiner, Pillemer & Thomsen, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, the successful completion of an activity for which these women did not previously feel adequately prepared for, facing the doubts raised by the activity and having the opportunity to reflect upon their life trajectories may have been positive and empowering aspects of this work that we had not anticipated in the design phase. Indeed, Steiner et al (2019) suggested that the conformation of life stories could increase the self-esteem of the participants. In our study, active involvement in carrying out an activity and the representation of their lives as a lifeline, generated a feeling of satisfaction and empowerment among the participants which ran adjacent to the subject we had set out to study.…”
Section: Discussionmentioning
confidence: 99%